2021
DOI: 10.1111/jhn.12859
|View full text |Cite
|
Sign up to set email alerts
|

Are older adults with excessive sodium intake at increased risk of hypohydration?

Abstract: Background Sodium intake is expected to affect water needs, although compensation mechanisms may not work efficiently particularly in older adults. The aim of this cross‐sectional study was to quantify the association between sodium excretion and hydration status in a representative sample of Portuguese older adults. Methods A cluster sampling approach was used, representing Portuguese older adults (≥65 years) according to sex, education level and region. From a sample size of 1500 participants, 1318 were elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
(76 reference statements)
1
2
1
Order By: Relevance
“…Unlike Gamba et al, who found that excessive sodium excretion was associated with an increased risk of hypohydration in men, suggesting that sodium intake may not be offset by the intake of water needed to excrete it [ 8 ], no significant statistical association was observed between excessive sodium excretion and hydration status in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike Gamba et al, who found that excessive sodium excretion was associated with an increased risk of hypohydration in men, suggesting that sodium intake may not be offset by the intake of water needed to excrete it [ 8 ], no significant statistical association was observed between excessive sodium excretion and hydration status in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Palmisano et al reported that, during the summer, older adults are more susceptible to dehydration [ 1 ]. The same was reported in women by Gamba et al [ 8 ]. Therefore, it can be speculated that the prevalence of hydration inadequacy in our population could be higher if samples had been collected in the summer, when more water is lost through transpiration and may not be adequately compensated by dietary intake.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations